NPR1 mediates a novel regulatory pathway in cold acclimation by interacting with HSFA1 factors. (October 2018) - Olate, Ema; Jiménez-Gómez, José; Holuigue, Loreto; Salinas, Julio
Abstract NON-EXPRESSER OF PATHOGENESIS-RELATED GENES 1 (NPR1) is a master regulator of plant response to pathogens that confers immunity through a transcriptional cascade mediated by salicylic acid and TGA transcription factors. Little is known, however, about its implication in plant response to abiotic stress. Here, we provide genetic and molecular evidence supporting the fact that Arabidopsis NPR1 plays an essential role in cold acclimation by regulating cold-induced gene expression independently of salicylic acid and TGA factors. Our results demonstrate that, in response to low temperature, cytoplasmic NPR1 oligomers release monomers that translocate to the nucleus where they interact with heat shock transcription factor 1 (HSFA1) to promote the induction of HSFA1-regulated genes and cold acclimation. These findings unveil an unexpected function for NPR1 in plant response to low temperature, reveal a new regulatory pathway for cold acclimation mediated by NPR1 and HSFA1 factors, and place NPR1 as a central hub integrating cold and pathogen signalling for a better adaptation of plants to an ever-changing environment. NPR1 is a highly conserved key regulator of SA-mediated immunity. Here, the authors show that it also plays an essential role in a previously unknown pathway that allows plants to adapt and acclimatize to cold temperatures.